Altitude training and recombinant human erythropoietin: Considerations for doping detection - Sutehall, S.; Muniz-Pardos, B.; Lima, G.; Wang, G.; Malinsky, F. R.; Bosch, A.; Zelenkova, I.; Tanisawa, K.; Pigozzi, F.; Borrione, P.; Pitsiladis, Y. (Current Sports Medicine Reports, 2019)
The benefit of training at altitude to enhance exercise performance remains equivocal although the most widely accepted approach is one where the athletes live and perform lower-intensity running at approximately 2300 m with high-intensity training at approximately 1250 m. The idea is that this method maintains maximal augmentations in total hemoglobin mass while reducing the performance impairment of high-intensity sessions performed at moderate altitude and thus preventing any detraining that can occur when athletes live and train at moderate altitude. This training regimen, however, is not universally accepted and some argue that the performance enhancement is due to placebo and training camp effects. Altitude training may affect an athlete's hematological parameters in ways similar to those observed following blood doping. Current methods of detection appear insufficient to differentiate between altitude training and blood doping making the interpretation of an athlete's biological passport difficult. Further research is required to determine the optimal method for altitude training and to enhance current detection methods to be able to differentiate better blood doping and altitude exposure.